Height Estimation Model for Eucalyptus tereticornis Grown under Semiarid Conditions of India - ., Ajit; Srivastava, Ritu; Jabeen, Nighat; Handa, A.K.; Singh, Rajendra; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
An experiment on structural analysis and modelling of Eucalyptusbased system was initiated at NRCAF, Jhansi in 2003 with three systems (agrisilviculture, block plantation and boundary plantation) and four clones obtained from ITC Bhadrachalam. To estimate the height of large trees, three types of models viz Richards, Schumacher, Allometric were attempted with dbh as predictor and the R2Â values were almost comparable in the three systems. However, when these models were extrapolated to examine their behaviour outside the observed range of dbh, the allometric function resulted in reasonably acceptable predictions even quite outside the observed range also, whereas the other two namely Richards and Schumacher leads to merely constant estimation for the extrapolated region. Accordingly, the allometric models are proposed for estimating the height values by simply measuring the dbh of the standing Eucalyptus trees in these systems.